2016
DOI: 10.1021/acssuschemeng.6b01488
|View full text |Cite
|
Sign up to set email alerts
|

Lignin Valorization through Thermochemical Conversion: Comparison of Hardwood, Softwood and Herbaceous Lignin

Abstract: In the present study, milled wood lignin (MWL) and organosolv lignin isolated from red oak (hardwood), loblolly pine (softwood) and corn stover (herbaceous biomass) were characterized by TGA, elemental analyzer, GPC, FTIR, 2D-HSQC NMR, and then pyrolyzed in the absence and presence of a zeolite catalyst. For all three biomass species, organosolv lignins contained fewer volatiles in comparison to the corresponding MWLs. Red oak lignin was affected most by the organosolv process, evident by the greatest decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
86
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 125 publications
(94 citation statements)
references
References 52 publications
8
86
0
Order By: Relevance
“…The T d ' s of the lignin were varied from 180 to 200.7 ° C for the three kinds of lignin, decreasing with increasing inorganic content in the lignin. The T d of corn stover lignin measured in this study was lower than that of softwood alkali lignin reported by Gordobil et al ., possibly attributed to the longer aliphatic side chains attached to aromatic rings . The range of T max was between 335.5 and 350.3 ° C for different corn stover lignin, which also decreased with increasing inorganic content.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The T d ' s of the lignin were varied from 180 to 200.7 ° C for the three kinds of lignin, decreasing with increasing inorganic content in the lignin. The T d of corn stover lignin measured in this study was lower than that of softwood alkali lignin reported by Gordobil et al ., possibly attributed to the longer aliphatic side chains attached to aromatic rings . The range of T max was between 335.5 and 350.3 ° C for different corn stover lignin, which also decreased with increasing inorganic content.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, corn stover‐derived lignin is one of the major byproducts in the biorefineries. It is also noteworthy that compared to woody‐biomass derived lignins, herbaceous biomass‐based lignin (such as corn stover lignin) has lower thermal stability and higher chemical reactivity due to its higher content of phenolic hydroxyl and branched aliphatic side chains . The aims of the present study are two folds: to investigate the role of the lignin impurities on the composite performance and evaluate the potential of the agricultural‐residue lignin in filler application.…”
Section: Introductionmentioning
confidence: 99%
“…The EHL had the highest molecular weight (i.e., M w = 1429 g/mol; M n = 746.18 g/mol). In a comparison of pretreatments on hardwood (red oak), softwood (loblolly pine), and herbaceous biomass (corn stover) for lignin valorization through pyrolysis, organosolv lignins contained fewer volatiles in comparison to the corresponding MWLs for all the tested samples [51]. Red oak lignin was affected mostly by the organosolv process, since the greatest decrease in volatile content and increase in carbon content were observed.…”
Section: 9mentioning
confidence: 99%
“…6,13 Lignin is an amorphous aromatic polymer and its physiochemical and thermal properties highly depend on the biomass origin and lignin isolation method. 14 Although lignin in general is biosynthesized from three main units, which are p-hydroxyphenyl (H), guaiacyl (G), and syringyl (S) units, the ratios of H, G, and S units vary by biomass species. 15 S unit is dominant in hardwood lignin; thus hardwood lignin is chemically stable and less likely to crosslink when it is thermally processed.…”
Section: Introductionmentioning
confidence: 99%